Conceptualisation of Time in Lithuanian - Juzelėnienė, Saulė (Kalbotyra, 2004)
The article aims at the investigation of time metaphors: the use and the expression of the concepts of time, the differences between the metaphorical use of time and its hyponyms. The donor zones investigated were such: time is moving object, time is space and time is an abstract.